MALDI-TOF Mass Spectrometry for interrogating ubiquitin enzymes - De Cesare, Virginia (Frontiers in Molecular Biosciences, 2023)
The attachment of ubiquitin to a substrate (ubiquitination or ubiquitylation) impacts its lifetime and regulates its function within the cell. Several classes of enzymes oversee the attachment of ubiquitin to the substrate: an E1 activating enzyme that makes ubiquitin chemically susceptible prior to the following stages of conjugation and ligation, respectively mediated by E2 conjugating enzymes (E2s) and E3 ligases (E3s). Around 40 E2s and more than 600 E3s are encoded in the human genome, and their combinatorial and cooperative behaviour dictate the tight specificity necessary for the regulation of thousands of substrates. The removal of ubiquitin is orchestrated by a network of about 100 deubiquitylating enzymes (DUBs). Many cellular processes are tightly controlled by ubiquitylation, which is essential in maintaining cellular homeostasis. Because of the fundamental role(s) of ubiquitylation, there is an interest in better understanding the function and specificity of the ubiquitin machinery. Since 2014, an expanding array of Matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) Mass Spectrometry (MS) assays have been developed to systematically characterise the activity of a variety of ubiquitin enzymes in vitro. Here we recapitulate how MALDI-TOF MS aided the in vitro characterization of ubiquitin enzymes and the discovery of new and unexpected of E2s and DUBs functions. Given the versatility of the MALDI-TOF MS approach, we foreseen the use of this technology to further expand our understanding of ubiquitin and ubiquitin-like enzymes.